A modified decal method for preparing the membrane electrode assembly of proton exchange membrane fuel cells. (1st January 2015) - Liang, Xiaolu; Pan, Guoshun; Xu, Li; Wang, Jiashu
Highlights: The complete transfer is achieved by optimizing the catalyst inks' composition and a hot peeling technique. The thickness of catalyst layers (before transfer) is consistent. The effects of drying methods, transfer pressure, test temperatures are explored and discussed. The MEAs show better performance. Abstract: Decal transfer is an effective method for fabricating membrane electrode assemblies (MEAs), due to its low interfacial resistance and applicability for mass production. Here we introduce a modified decal method which makes it possible and convenient to achieve complete decal transferring. The composition of catalyst inks, drying process and transfer pressure are optimized in detail. During catalyst ink preparation, the viscosity is adjusted by altering the composition of the solvents to obtain catalyst layers (before transfer) with continuous thickness. In addition, MEAs whose catalyst layers (before transfer) were dried in four different ways are tested for application in a proton exchange membrane fuel cell. The transfer pressure is also optimized on the basis of the two previous conditions and the MEAs fabricated by this modified method show simplicity to achieve complete transfer in decal method, good repeatability and improvement in cell performance.